Social Distancing and Economic Crisis During COVID-19 Pandemic Reduced Cancer Control in Latin America and Will Result in Increased Late-Stage Diagnoses and Expense. (2021) - Vázquez Rosas, Tabaré; Cazap, Eduardo; Delgado, Lucía; Ismael, Julia; Bejarano, Suyapa; Castro, Carlos; Castro, Hugo; Müller, Bettina; Gutiérrez-Delgado, Francisco; Santini, Luiz Antonio; Vallejos Sologuren, Carlos
Abstract : Since December 2019, the world has been mired in an infectious pandemic that has displaced other health priorities for 21st century populations. Concerned about this situation, Latin American experts on cancer decided to evaluate the impact of the pandemic on cancer control in the region. The analysis was based on information obtained from public sources and scientific publications and included the characteristics of the health care and cancer control prior to the pandemic, the COVID-19 pandemic and measures implemented by the governments of the region, and the regional impact of the pandemic on cancer control together with the costs of cancer care and possible impact of the pandemic on cancer expense. We compared 2019 and 2020 data corresponding to the period March 16-June 30 and found a significant reduction in the number of first-time visits to oncology services (variable depending on the country between –28% and –38%) and a corresponding reduction in pathology (between –6% and –50%), cancer surgery (between –28% and –70%), and chemotherapy (between –2% and –54%). Furthermore, a significant reduction in cancer screening tests was found (PAP smear test studies: between –46% and –100%, mammography: between –32% and –100%, and fecal occult blood test: –73%). If this situation becomes a trend, the health and economic impact will be compounded in the postpandemic period, with an overload of demand on health services to ensure diagnostic tests and consequent treatments. On the basis of this information, a set of prevention and mitigation measures to be immediately implemented and also actions to progressively strengthen health systems are proposed.